Hyper cross‐linked polymers containing amino group functionalized polyimide mixed matrix membranes for gas separation. Issue 20 (20th January 2022) - Li, Weixin; Peng, Longfei; Li, Yinhui; Chen, Zan; Duan, Cuijia; Yan, Shuo; Yuan, Biao
Abstract: The design and synthesis of porous materials with novel structures and functional groups to prepare mixed matrix membranes (MMMs) is an effective way to break through trade‐off effect of membrane technology. Here, hyper cross‐linked polymers containing amino groups (HCPs‐NH2 ) with philic‐CO2 frame were successfully prepared for the fabrication of polyimide (PI)/HCPs‐NH2 MMMs. The separation performance of pure gas is studied in order to explore NH2 groups facilitating CO2 diffusion and transmission and enhancing CO2 permeability. Consequently, the permeability of the PI/HCPs‐NH2 MMMs toward CO2 and O2 are 77.56 Barrer and 17.91 Barrer versus pure PI film toward CO2 and O2 (62.42 Barrer and 13.85 Barrer). The selectivity for CO2 /CH4 and O2 /N2 pairs is 24.44 and 4.01, and the selectivity of pure PI film toward CO2 /CH4 and O2 /N2 pairs is 20.76 and 3.29, respectively. The permeability and selectivity of PI/HCPs‐NH2 MMMs are higher than pure PI film breaking through the trade‐off effect. Moreover, the PI/HCPs‐NH2 MMMs show better separation performance on the CO2 /CH4 pair than the O2 /N2 pair, indicating HCPs‐NH2 with philic‐CO2 frame plays a very important role in promoting CO2 permeability. Thus, the PI/HCPs‐NH2 MMMs have potential applications in the field of natural gas purification. Abstract :